Origen’s Polemics in "Princ" 4.2.4: Scriptural Literalism as a Christo-Metaphysical Error - Wood, Jordan Daniel (Vigiliae Christianae, 2015)
The relation between Books 1-3 and Book 4 of Origen’s Peri Archon has largely been left unspecified or denied. This is due to the apparent incongruence between the metaphysical discussions of the former section and the hermeneutical remarks of the latter. I argue that Origen’s threefold distinction of Scripture in Princ 4.2.4 draws upon key metaphysical conclusions of the earlier sections to depict the metaphysical structure of inspired Scripture as analogous to the Incarnation, and that this insight constitutes Origen’s fundamental polemic against scriptural literalism, the common error of the two primary adversaries of the work (the “simple” of the Church and the Marcionites). Peri Archon is thus unified around the polemical purpose of defending Origen’s allegorical exegesis.